2018
DOI: 10.1039/c8ra08811j
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale screening of novel biobased monomers: the curious case of 1,3-cyclopentanediol

Abstract: In this work, we report on the small scale polycondensation and consecutive analysis of novel polyesters based on the potentially renewable 1,3-cyclopentanediol (CPdiol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Therefore, the stability of this newly formed group can be promising to protect otherwise labile amine and/or acid functionalities. For example, as is reported in previous work, the potentially renewable cis / trans 1,3-cyclopentanediamines are prone to degrade (by oxidation and dehydration) at elevated temperatures, similar to their diol counterparts cis / trans 1,3-cyclopentanediols (Noordzij et al, 2018). This instability makes the use of these monomers via melt-polycondensation reactions challenging as the final products are heavily colored and either have low molecular weights or are cross-linked (Noordzij et al, 2018).…”
Section: State Of the Artsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, the stability of this newly formed group can be promising to protect otherwise labile amine and/or acid functionalities. For example, as is reported in previous work, the potentially renewable cis / trans 1,3-cyclopentanediamines are prone to degrade (by oxidation and dehydration) at elevated temperatures, similar to their diol counterparts cis / trans 1,3-cyclopentanediols (Noordzij et al, 2018). This instability makes the use of these monomers via melt-polycondensation reactions challenging as the final products are heavily colored and either have low molecular weights or are cross-linked (Noordzij et al, 2018).…”
Section: State Of the Artsupporting
confidence: 67%
“…For example, as is reported in previous work, the potentially renewable cis / trans 1,3-cyclopentanediamines are prone to degrade (by oxidation and dehydration) at elevated temperatures, similar to their diol counterparts cis / trans 1,3-cyclopentanediols (Noordzij et al, 2018). This instability makes the use of these monomers via melt-polycondensation reactions challenging as the final products are heavily colored and either have low molecular weights or are cross-linked (Noordzij et al, 2018). Instead, when reacting these monomers with itaconic acid, thermally stable dicarboxylic acid monomers are obtained that can readily be used in melt-polycondensation reactions (Noordzij et al, 2019).…”
Section: State Of the Artsupporting
confidence: 67%
“…Cycloaliphatic diols such as 4b are interesting building blocks for novel jet fuels, 15 surfactants, 16 and particularly specialized polymers. 13 , 17 Their molecular structure is moderately rigid and consists of at least two diastereoisomers, namely, cis and trans (as primary classification). For related polyesters, it has been shown that the incorporation of larger relative portions of the cyclic trans -monomer generally leads to polymeric materials with higher crystallinity and glass-transition temperatures ( T g ).…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 19 For these polyesters made from 4b , the cis – trans ratio of the cyclopentane ring units also affects the degradation temperature as the ester groups of cis -units are more susceptible to dehydrative decomposition than those of trans -units. 17 …”
Section: Introductionmentioning
confidence: 99%
“…To this end, we designed, and 3D-printed linear and circular vial holders for 10 and 20 vials respectively. The circular vial holder is expected to ensure identical stirring conditions and thus, maximize the reproducibility and reliability of small-scale screening experiments, [31][32][33][34][35] where small differences may attract significant attention. In addition, the vial holders can be scaled up or down easily (using the software corresponding to the 3D printer of choice) to handle larger or smaller reaction vials.…”
Section: Introductionmentioning
confidence: 99%